(Z)-Amino(2-methyl-3-oxoisoindolin-1-ylidene)acetonitrile - Till Opatz; Dorota Ferenc; Dieter Schollmeyer (Acta Crystallographica Section E, 2009)
The asymmetric unit of the title compound, C11H9N3O, contains two independent and nearly identical molecules (A and B). Molecule A can be transformed to B using a rotation of approximately 85° around the [111] direction. Each A molecule is connected to three B molecules via N—H...N and N—H...O hydrogen bonds and vice versa. Centrosymmetrically related molecules of the same residue form π–π interactions with centroid–centroid distances of 4.326 (1) and 3.826 (1) Å for the benzene rings of molecules A and B, respectively.